Turnover de carbono nos tecidos de frangos de corte em diferentes fases de crescimento - Ducatti, Carlos [UNESP]; Mituo, Mariela Akie Okino; Denadai, Juliana Célia; Martins, Marcela Buosi; Souza-kruliski, Cibele Regina De; Pelícia, Vanessa Cristina; Sartori, José Roberto [UNESP] (Universidade Federal de Santa Maria, 2014)
The aim of this study was to evaluate carbon turnover on muscle tissue Pectoralis major, keel, tibia and liver of poultry at different life stages using the carbon stable isotopes technique. 216 male chick lings (Cobb) were used. The trial was conduced in a totally random distribution consisting on seven treatments with distinct days for diet substitution (0, 7, 14, 21, 28, 35, 42 days old). Either Boltzmann sigmoid regression or the exponential time function were used in order to measure the carbon isotopic turnover in a specific period of time. The half-life were: 2.5; 2.8; 2.9; 4.9; 5.1; 5.5 e 6.0 day on muscle tissue; 2.7; 2.9; 3.1; 4.6; 5.3; 4.1 e 8.0 day on keel; 4.4; 3.6; 5.4; 5.8; 4.3; 5.2 e 6.3 day on tibia and 1.3; 1.9; 1.4; 1.5; 1.9; 1.7 and 2.1 day on liver, for to treatments T1, T2, T3, T4, T5, T6 e T7 respectively. According to the results of this study, it is possible to conclude that the tibia has slowest metabolism and may indicate the isotopic signature of initial diets of poultry culture. The fast metabolism tissue, liver, is appropriated to reflect the diets fed at closer period of evaluation.

Este trabalho objetivou determinar o turnover do carbono no Pectoralis major, quilha, tíbia e fígado de frangos de corte em seus diferentes períodos de crescimento, utilizando a técnica dos isótopos estáveis. Foram utilizados 216 pintos de corte, machos, Cobb. O delineamento experimental foi inteiramente casualizado e consistiu de sete tratamentos com dias de substituição das dietas distintos: 0; 7; 14; 21; 28; 35; 42 dias de idade. Para mensurar o turnover do carbono nos tecidos em determinado intervalo de tempo, foi utilizado o modelo sigmoidal de regressão de Boltzmann ou função exponencial do tempo. Os valores de meias-vidas foram: 2,5; 2,8; 2,9; 4,9; 5,1; 5,5 e 6,0 dias para músculo peitoral; 2,7; 2,9; 3,1; 4,6; 5,3; 4,1 e 8,0 dias para quilha; 4,4; 3,6; 5,4; 5,8; 4,3; 5,2 e 6,3 dias para tíbia e 1,3; 1,9; 1,4; 1,5; 1,9; 1,7 e 2,1 dias para fígado, nos tratamentos T1, T2, T3, T4, T5, T6 e T7, respectivamente. Pode-se concluir que a tíbia possui metabolismo lento e pode indicar o sinal isotópico das dietas iniciais da criação dos frangos de corte; e o fígado, metabolismo rápido, indicado para refletir a dieta próxima da fase de avaliação.
Carbon turnover in poultry tissues at different growth stages
Keywords: half-life; isotopic dilution; isotope 13C; diluição isotópica; isótopo 13C; meia-vida